The Notary Responsibilities for Delay in Registration of the Fiduciary Guarantee Deed - Japar, Abdul (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to analyze how Notaries are responsible for late registration of Fiduciary Guarantees carried out by Corporations. The approach method in this study uses a Juridical Sociological approach and is analytically descriptive in nature. The results of the study show that if there is a delay in registering a fiduciary guarantee, for the sake of legal certainty and as an effort to resolve the delay in registering a fiduciary guarantee object, it is by making a new Fiduciary Guarantee Deed by presenting all the parties concerned to the fiduciary agreement or a notary can also provide other solutions such as making the Affirmation Deed on the Fiduciary Guarantee Deed that was previously made. Based on the Affirmation Deed, fiduciary guarantees that were previously registered late can be immediately registered by the Financing Company.Keywords: Fiduciary; Guarantee; Registration.